2011
DOI: 10.1373/clinchem.2010.161125
|View full text |Cite
|
Sign up to set email alerts
|

Human Pro–B-Type Natriuretic Peptide Is Processed in the Circulation in a Rat Model

Abstract: BACKGROUND:The appearance of B-type natriuretic peptide (BNP) in the blood is ultimately caused by proteolytic processing of its precursor, proBNP. The mechanisms leading to the high plasma concentration of unprocessed proBNP are still poorly understood. The goals of the present study were to examine whether processing of proBNP takes place in the circulation and to evaluate the clearance rate of proBNP and proBNPderived peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…Unprocessed proBNP, however, exhibits markedly reduced physiological activity compared with BNP and is currently considered to be insufficient to promote an adequate physiological natriuretic hormone response in HF patients (6 ). Our previous studies in rats have revealed that processing of proBNP in the circulation is possible (33 ). Given this, the influence of LCZ696 on the efficiency of proBNP processing, giving rise to bioactive BNP, appears also to be important to evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…Unprocessed proBNP, however, exhibits markedly reduced physiological activity compared with BNP and is currently considered to be insufficient to promote an adequate physiological natriuretic hormone response in HF patients (6 ). Our previous studies in rats have revealed that processing of proBNP in the circulation is possible (33 ). Given this, the influence of LCZ696 on the efficiency of proBNP processing, giving rise to bioactive BNP, appears also to be important to evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high circulating concentrations of proBNP in patients with heart failure have led to speculation that proBNP may be processed in blood or tissues to provide an additional supply of circulating or tissue BNP [78,93,94]. This speculation is supported by results from two studies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the control group (n=3), animals were treated with the vehicle solution (intravenously). In the treated group (n=3), animals were treated (intravenously) with 12 nmol/kg of human BNP (hBNP) (Genscript, NJ), at a dose that has been previously demonstrated to increase the endogenous levels of BNP in rats 24. For BNP dissolution, powder was dissolved in a minimal amount of 50 mmol/L Na‐acetate buffer, and then resuspended in saline, and the pH was adjusted to 7.4. hBNP concentration was adjusted to inject 1 mL of treatment per animal.…”
Section: Methodsmentioning
confidence: 99%